MODEL OF THE FLAT FAIRING ANTENNA DIELECTRIC LAYER WITH AERODYNAMIC HEATING - Kozlovskiy, Valerii; Kozlovskiy, Valeriy; Nimych, Oleksii; Klobukova, Lyudmila; Yakymchuk, Natalia (My University, 2023)
To protect the antenna systems of modern aircraft, radio-transparent dielectric fairings are widely used. At low flight speeds, when designing and evaluating the characteristics of the fairing-antenna, it is assumed that the dielectric constant is a constant value and does not depend on the aircraft's flight speed. As the flight speed increases, as a result of aerodynamic heating of the fairing, its dielectric permeability changes, which leads to errorsin the processing of received signals. Currently, to take into account the effect of dielectric coatings heating when designing antenna systems,the temperature of the fairing wall is averaged over its thickness. This method during maneuvering and at high flight speeds leads to large errorsin determining the characteristics of the fairing antenna since the nature of the temperature distribution along the thickness of the fairing wall is not taken into account. A new approach to the analysis of dielectric layers with their uneven heating along the thickness is proposed. The obtained results makeit possible to adjust the signal processing algorithms with analog and digital matrices, as a result of taking into account the emerging heat flows affecting the fairing of the aviation antenna, which leads to the improvement of the characteristics of the antenna systems.
Keywords: aviation antenna; dielectric layer; aerodynamic heating; wave resistance; quadrupole